Phenotypic Variability in iPSC-Induced Cardiomyocytes and Cardiac Fibroblasts Carrying Diverse LMNA Mutations - Yang, Jiajia; Argenziano, Mariana A.; Burgos Angulo, Mariana; Bertalovitz, Alexander; Beidokhti, Maliheh Najari; McDonald, Thomas V. (Frontiers in Physiology, 2021)
Mutations in the LMNA gene (encoding lamin A/C) are a significant cause of familial arrhythmogenic cardiomyopathy. Although the penetrance is high, there is considerable phenotypic variability in disease onset, rate of progression, arrhythmias, and severity of myopathy. To begin to address whether this variability stems from specific LMNA mutation sites and types, we generated seven patient-specific induced pluripotent stem cell (iPSC) lines with various LMNA mutations. IPSC-derived cardiomyocytes (iCMs) and cardiac fibroblasts (iCFs) were differentiated from each line for phenotypic analyses. LMNA expression and ERK pathway activation were perturbed to differing degrees in both iCMs and iCFs from the different lines. Enhanced apoptosis was observed in iCMs but not in iCFs. Markedly diverse irregularities of nuclear membrane morphology were present in iCFs but not iCMs, while iCMs demonstrated variable sarcomere disarray. Heterogenous electrophysiological aberrations assayed by calcium indicator imaging and multi-electrode array suggest differing substrates for arrhythmia that were accompanied by variable ion channel gene expression in the iCMs. Coculture studies suggest enhancement of the LMNA mutation effects on electrophysiological function exerted by iCFs. This study supports the utility of patient-specific iPSC experimental platform in the exploration of mechanistic and phenotypic heterogeneity of different mutations within a cardiac disease-associated gene. The addition of genetically defined coculture of cardiac-constituent non-myocytes further expands the capabilities of this approach.